2018
DOI: 10.1111/jpy.12760
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and molecular phylogeny of epizoic araphid diatoms on marine zooplankton, including Pseudofalcula hyalina gen. & comb. nov. (Fragilariophyceae, Bacillariophyta)

Abstract: Some diatoms are able to colonize as epibionts on their potential zooplankton predators. Here, we report Pseudohimantidium pacificum living on the copepod Corycaeus giesbrechti and as a new finding on Oithona nana, Protoraphis atlantica living on the copepod Pontellopsis brevis, Protoraphis hustedtiana on the cypris larvae of barnacles, and Falcula hyalina on the copepod Acartia lilljeborgii. The epizoic diatoms were able to grow as free-living forms under culture conditions. Pseudohimantidium pacificum and P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Hernández-Becerril [51] reported that the valves of C. tetrastichon were less heavily silicified than the other member of the subgenus Phaeoceros. A reduction of the silicification has been also observed in other epizoic species as compared with benthic counterparts [31].…”
Section: Symbiotic Diatomsmentioning
confidence: 68%
See 3 more Smart Citations
“…Hernández-Becerril [51] reported that the valves of C. tetrastichon were less heavily silicified than the other member of the subgenus Phaeoceros. A reduction of the silicification has been also observed in other epizoic species as compared with benthic counterparts [31].…”
Section: Symbiotic Diatomsmentioning
confidence: 68%
“…The live plankton concentrate was scanned in settling chambers with inverted microscopes. Detailed methods of collection and observations are described in Gómez et al [22,31]. References were used for the identification of diatoms [10], cyanobacteria [12], naked ciliates [21,22,32], and tintinnid ciliates based on the lorica features [3,4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, occurrences of microalga epibiosis on copepods were mostly documented with particular focus on epibiont morphology, phylogeny, and distribution (Carman and Dobbs, 1997;Fernandes and Calixto-Feres, 2012;Li et al, 2014;Gómez et al, 2018;Nayak et al, 2021). The impacts of algal epibiosis on copepod reproduction were rarely investigated as yet.…”
Section: Introductionmentioning
confidence: 99%